双盘式渐开线测试仪无回差传递杠杆的设计 - 李树伟; 马勇; 娄志峰 (Jixie chuandong)
The technology of involutes tooth profile measurement for master gear is important and difficult in its all precision indexes.The double-disc measuring apparatus of involutes tooth profile was provided with high accuracy.The principle of the measuring apparatus was introduced and analyzes the feasibility of "The Transmission lever of no hysteretic error"which was used in the Measuring Apparatus was analyzed.In conclusion,it was proved very sensitive to micro-error and can feel content to the measuring apparatus of involutes tooth profile in benchmark step.Benchmark.